COMPOSITION AND IMPROVEMENT OF METHODOLOGY OF DESCRIPTION IN THE PROFESSIONAL TRAINING OF FUTURE FINE ART TEACHERS FOR PEDAGOGICAL ACTIVITY - Baxriyev Ilxomjon Saidazimovich; Bakhriyev Ilhomjon Saidazimovich (Galaxy International Interdisciplinary Research Journal, 2021)
The summary of the article contains recommendations on the meaningful organization of the teaching process, the meaningful organization of lessons on the basis of new pedagogical technologies. There is also a definition of innovative technology.